2003
DOI: 10.1177/152660280301000331
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Treatment of Long Superficial Femoral Artery Occlusive Disease: Efficacy of the Hemobahn Stent-Graft

Abstract: Symptomatic long occlusive lesions of the SFA treated percutaneously with the Hemobahn stent-graft achieved good outcomes initially with a low complication rate. Primary and secondary patencies were similar to those reported for open synthetic femoropopliteal bypass procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 54 publications
1
29
0
1
Order By: Relevance
“…Percutaneous angioplasty, because of the progress of the intraluminal and the extraluminal techniques and the availability of new materials, has demonstrated great efficacy in the treatment of CLI in terms of success rate, clinical outcome, and procedure-related complications [4,5,16].…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous angioplasty, because of the progress of the intraluminal and the extraluminal techniques and the availability of new materials, has demonstrated great efficacy in the treatment of CLI in terms of success rate, clinical outcome, and procedure-related complications [4,5,16].…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42][43][44] However, the early and midterm outcomes with the Hemobahn TM stent-graft (WL Gore and Associates, Inc., Flagstaff, AZ, USA) seem to be competitive with prosthetic surgical bypass with a reduced inflammatory vessel wall response. [45][46][47][48][49][50][51][52][53] Recently, the TCT (Trans Catheter Therapeutics) 2006 meeting presented promising single-centre registry data on the 1-year patency of the Viabahn TM (WL Gore and Associates, Inc.) application in long native SFA lesions and on in-stent lesions too being 90% and 65%, respectively. 54,55 Moreover, Saxon et al 56 reported a 79% primary patency rate and 93% secondary patency rate at the 4-year follow-up for lesions of an average length Ͼ10 cm, using Hemobahn or Viabahn stent grafts.…”
mentioning
confidence: 99%
“…Prosthetic stent-grafts, mostly utilizing ePTFE, have been shown to have poor 1-year patency rates. 4,5 Other designs employed saphenous vein as a lining, but patency rates were poor, and other logistical issues arose due to limited lumen diameter and concerns about tissue thickness.…”
Section: Discussionmentioning
confidence: 99%